The influence of emissions scenarios on future Antarctic ice loss is unlikely to emerge this century - Lowry, Daniel P.; Krapp, Mario; Golledge, Nicholas R.; Alevropoulos-Borrill, Alanna (Communications earth & environment, 2021)
Of all the components of the global sea-level budget, the future contribution of the Antarctic Ice Sheet is the most uncertain in sea-level rise projections. Dynamic ice sheet model simulations show considerable overlap in the projected Antarctic Ice Sheet sea-level contribution under various greenhouse gas emissions scenarios and the timescale at which scenario dependence will emerge is unclear. With historically constrained ice sheet simulations and a statistical emulator, we demonstrate that a high-emissions signature of the Antarctic Ice Sheet sea-level contribution will not unambiguously emerge from the wide potential range of low-emission sea-level projections for over 100 years due to current limitations in our understanding in ice flow and sliding. However, the results also indicate that the total global warming that occurs over the 21st century controls the resulting long-term Antarctic Ice Sheet sea-level commitment, with multi-meter differences between the highest and lowest emissions scenarios in subsequent centuries.